Design of a prospective patient‐level pooled analysis of two parallel trials of empagliflozin in patients with established heart failure. (14th December 2020) - Packer, Milton; Butler, Javed; Filippatos, Gerasimos; Zannad, Faiez; Ferreira, Joao Pedro; Zeller, Cordula; Brueckmann, Martina; Jamal, Waheed; Pocock, Stuart J.; Anker, Stefan D.; ,
Abstract : Aim: The EMPEROR‐Reduced trial demonstrated that empagliflozin reduced the combined risk of cardiovascular death or hospitalization for heart failure in patients with a reduced ejection fraction, and the EMPEROR‐Preserved trial is currently evaluating the effect of the drug on the same endpoint in patients with an ejection fraction >40%. However, neither the trial was designed to have adequate statistical power to evaluate the effects of empagliflozin and dapagliflozin on major adverse renal outcomes or on mortality. Herein we describe the design of a prospective individual patient‐level pooled analysis of two large‐scale trials with empagliflozin (EMPEROR‐Reduced and EMPEROR‐Preserved) in patients with heart failure across the spectrum of ejection fraction. Methods: The trials were carried out in parallel using the same administrative structure and committees, randomization procedure, schedule of study visits and adjudication criteria and similar groups of investigators and case report forms. The two component trials specified the same primary and key secondary endpoints and used an identical hierarchical testing procedure, which included a pooled analysis of the two trials as a key component of the hierarchy. Consequently, the pooled analysis has been prospectively assigned a false positive error rate, which is conditional on one or both trials first achieving success on their primary and one or both key secondary endpoints. The pooled analysis has its own statistical plan with its own endpoints, and this plan was finalized before either trial had begun recruitment of patients into either study. The primary endpoint of the pooled analysis is a composite of serious adverse renal outcomes, defined by chronic dialysis, renal transplantation and a profound or sustained decrease in glomerular filtration rate. All‐cause and cardiovascular mortality are specified as secondary endpoints. Conclusion: The planned pooled analysis has an unusually high degree of statistical rigour that will allow it to address important questions that cannot be fully addressed by the individual trials.